Isolation and diagnosis of the pathogens causing seed decay and damping-off disease on wheat and control them using some biological and chemical factors - عبد علي الموسوي, محسن; عبد الجليل لهوف, عدنان; هادي جعفر, علا (Journal of Kerbala for Agricultural Sciences, 2017)
This study was conducted to isolate and identify the causal agents of seed decay and damping-off disease on wheat. Additionally, the biological factor Bacillus thurigensis (BT), the chemical induction factor BION (BI) and the extract of sea algae (MU) were evaluated in control of this disease. After isolation process, the cultural features of the fungal isolates were investigated and their pathogenicity was assessed. The PCR technique was operated also to study the most pathogenic fungal isolates. Subsequently, the efficiency of the above three factors were evaluated in control of the disease in the plastic house. The results showed that the pathogens of this disease were belonging to two fungal genus Rhizoctonia and Fusarium. As well as, all fungal isolates were highly pathogenic. Pure DNA with enough quantity was extracted from these fungal isolates in order to conduct a PCR reaction after manipulating of the DNA extraction process. The results displayed also good inhibition ability of the BT against all pathogenic fungal isolates with inhibition percentage ranged between 68.05-87.21%. Additionally, the biological and chemical factors selected in this study proved their efficiency in controlling of this disease particularly when they were applied in integrated method. F1+BI+MU+BT and R1+BI +MU+BT treatments caused the highest percentage of seed germination reached 100% and 93.33% in addition to the lowest percentages of seed decay and damping-off 0% in both of them and disease severity 17% and 19.33% respectively. Furthermore, the growth characteristics of wheat plants were significantly improved comparing with the Benlet fungicide treatment in plastic house experiment. The data of this study may indicate to possibility of applying these three factors together to control the seed decay and damping-off disease and possibility preserving of the environment simultaneously.